Hemorrhagic Reversible Cerebral Vasoconstriction Syndrome: Features and Mechanisms. Issue 7 (July 2016) - Topcuoglu, Mehmet A.; Singhal, Aneesh B.
Abstract : Background and Purpose—: To compare hemorrhagic and nonhemorrhagic reversible cerebral vasoconstriction syndromes (RCVS) with a view to understand mechanisms. Methods—: This single-center retrospective study included 162 patients with RCVS. Clinical, brain imaging, and angiography data were analyzed. Results—: The mean age was 44±13 years, 78% women. Hemorrhages occurred in 43% including 21 patients with intracerebral hemorrhage (ICH) and 62 with convexal subarachnoid hemorrhage (cSAH). The frequency of triggers (eg, vasoconstrictive drugs) and risk factors (eg, migraine) were not significantly different between hemorrhagic and nonhemorrhagic RCVS or between subgroups (ICH versus non-ICH, isolated cSAH versus normal scan). Hemorrhagic lesions occurred within the first week, whereas infarcts and vasogenic edema accumulated during 2 to 3 weeks ( P <0.001). Although all ICHs occurred before cSAH, their time course was not significantly different ( P =0.11). ICH and cSAH occurred earlier than infarcts ( P ⩽0.001), and ICH earlier than vasogenic edema ( P =0.009). Angiogram analysis showed more severe vasoconstriction in distal versus proximal segments in all lesion types (ICH, cSAH, infarction, vasogenic edema, and normal scan). The isolated infarction group had more severe proximal vasoconstriction, and those with normal imaging had significantly less vasoconstriction. Multivariable analysis failed to uncover independent predictors of hemorrhagic RCVS; however, female sex predicted ICH ( P =0.048), and angiographic severity predicted infarction ( P =0.043). Conclusions—: ICH and cSAH are common complications of RCVS. Triggers and risk factors do not predict lesion subtype but may alter central vasomotor control mechanisms resulting in centripetal angiographic evolution. Early distal vasoconstriction is associated with lobar ICH and cSAH, and delayed proximal vasoconstriction with infarction.